Pengetahuan dan Praktik Konsumsi Herbal dan Rempah pada Masyarakat Semarang - Yurisa Aprilia Athory; Nico Andreas (Universitas Padjadjaran, 2018)
Herbs and spices are common ingredients used by people for daily consumption and useful for maintaining a healthy body, preventing and treating various types of diseases. This research aims to see the knowledge of the people of Semarang in the Chinatown area in processing herbs and spices, as well as their practice in consuming these ingredients. This research was conducted using a qualitative approach, ethnographic design to describe in-depth and detail the knowledge and practice of Chinatown people in consuming herbs and spices. This research used an emic perspective: the perspective of the community. The results of this study found that the knowledge of the Chinatown community about herbs and spices is obtained from oral stories passed down from generation to generation (exemplified from parents to children), personal experiences, and stories of friends or relatives, and information obtained from the internet. Meanwhile, the practice of using herbs and spices is carried out to treat the illness or to prevent the disease.